2014
DOI: 10.1103/physrevb.90.094305
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond strain dynamics inGe2Sb2Te5monitored by time-resolved x-ray diffraction

Abstract: Coherent phonons (CPs) generated by laser pulses on the femtosecond scale have been proposed as a means to achieve ultrafast, nonthermal switching in phase-change materials such as Ge 2 Sb 2 Te 5 (GST). Here we use ultrafast optical pump pulses to induce coherent acoustic phonons and stroboscopically measure the corresponding lattice distortions in GST using 100-ps x-ray pulses from the European Synchrotron Radiation Facility (ESRF) storage ring. A linear-chain model provides a good description of the observed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…using free-electron lasers, shows promise. Indeed, it was recently found that the photo-induced change in the diffraction peak intensity under intense sub-picosecond excitation of GeTe in the pre-amorphisation regime could not be explained by considering only heating effects and assuming an unchanged average structure52. We believe, however, that one of the best methods to provide spectroscopic signatures for the TCBs would be femtosecond time-resolved EXAFS measurements, because EXAFS is an element selective local probe that takes a snapshot of the structure on the 10 −15  sec.…”
Section: Resultsmentioning
confidence: 99%
“…using free-electron lasers, shows promise. Indeed, it was recently found that the photo-induced change in the diffraction peak intensity under intense sub-picosecond excitation of GeTe in the pre-amorphisation regime could not be explained by considering only heating effects and assuming an unchanged average structure52. We believe, however, that one of the best methods to provide spectroscopic signatures for the TCBs would be femtosecond time-resolved EXAFS measurements, because EXAFS is an element selective local probe that takes a snapshot of the structure on the 10 −15  sec.…”
Section: Resultsmentioning
confidence: 99%
“…As for the estimation of the temperature, it is worth mentioning that the possible effect of the latent heat associated with the phase transition, and the contribution of the radiative recombination of the charge carriers have not been considered, and because of this the temperatures calculated within the TTM model described above overestimates the real values, as also observed in recent time-resolved x-ray diffraction studies. 12 Nevertheless, a correct estimation of the lattice temperature can be reliably obtained from the intensity and peak-position data at long delay time (~ 400 ps), as shown in the main text in Figs. 3b and 3d.…”
Section: Modified Two-temperature Modelmentioning
confidence: 97%
“…The dynamics of this ultrafast phase transition in GST has been studied using time-resolved spectroscopy12131415, and x-ray and electron diffraction1617. Time-resolved optical studies have demonstrated that the optical index of GST changes from opaque to transparent within 1 ps after near-infrared (IR) photoexcitation, with a clear threshold in the fluence of the incident laser for permanent amorphization1213.…”
mentioning
confidence: 99%
“…A germanium atom travels approximately 0.29 nm from an octagonal to a tetragonal site in this process. Acoustic phonon propagation and thermally limited amorphization have been observed by time-resolved x-ray and electron diffraction experiments with near-IR photoexcitation1617. In essence, the thermal nature of the laser-induced amorphization of GST deduced from crystallographic methods conflicts with the results obtained from time-resolved x-ray and optical spectroscopy915.…”
mentioning
confidence: 99%